Avatar Creation: The Social Construction of "Beauty" in Second Life. (September 2018) - Mills, Hailey L.
Rooted in the theory of Social Construction of Reality and informed by media portrayal of female beauty and virtual community research, this study examined how beauty is socially constructed by gatekeepers in Second Life. A content analysis of 360 still images of female avatars was conducted to understand the extent to the beauty types that appear in the virtual world. Findings suggest trendy and sex kitten/sensual beauty types were the most-portrayed beauty types. Most female avatars had the ideal body size and light colored skin. In addition, this study found a significant difference in beauty type among different types of products.